2019
DOI: 10.31234/osf.io/afz6b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Master Narrative Identity Development in Cultural Context: The Role of Deviating from Master Narratives.

Abstract: Objective: The great majority of research on identity and personality development has focused on individual processes of development, to the relative neglect of the cultural context of development. We employ a recently articulated framework for the examination of identity development in context, centered on the construct of master narratives, or culturally shared stories. Method: Across three studies we asked emerging and mid-life adults (n = 512) to narrate personal experiences of deviations from these maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…How should we understand that some cultured agents seek and tolerate the uncertainty of questioning their identity beyond social norms and voluntarily go about a long process of thinking autonomously about themselves, rather than using norms as an antidote to this uncertainty? Mclean and colleagues (McLean & Syed 2015;McLean et al 2017) make similar observations in their research on identity development, which focus on the relationship of identity and society in personal narratives. This team focuses on the narratives that are the cultural templates for the experiences one should expect to have in their lives, which they call master narratives.…”
Section: Introductionmentioning
confidence: 82%
“…How should we understand that some cultured agents seek and tolerate the uncertainty of questioning their identity beyond social norms and voluntarily go about a long process of thinking autonomously about themselves, rather than using norms as an antidote to this uncertainty? Mclean and colleagues (McLean & Syed 2015;McLean et al 2017) make similar observations in their research on identity development, which focus on the relationship of identity and society in personal narratives. This team focuses on the narratives that are the cultural templates for the experiences one should expect to have in their lives, which they call master narratives.…”
Section: Introductionmentioning
confidence: 82%
“…The framework suggests that one mechanism of change and rigidity comes through personal identity development processes, with greater identity work particularly important for processes of change. For example, those who are engaged with alternative narratives are also engaged with more identity work (McLean et al, 2017a; McLean, Shucard, & Syed, 2017b). Another obvious developmental mechanism of change and rigidity is socialization, which has not yet been empirically addressed within the master narrative framework.…”
Section: The Relation Between Identity Development and Master Narratimentioning
confidence: 99%
“… RQ2: Are narrative patterns in the deviations related to identity development processes (Study 1a)? We expected that those who deviated and elaborated an alternative narrative would report greater identity development processes (McLean et al, 2017a, 2017b), specifically – making more explicit narrative connections between an event and the self, and higher scores on identity exploration. RQ3: How are master narratives negotiated and socialized? We addressed this through interviews about retrospective reports of perceptions of socialization experiences (Study 1b), and observations of mother–adolescent conversations (Study 2).…”
Section: Present Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A particularly relevant result is that individuals who develop alternative narratives (i.e., changed relative to the master narrative) are also engaged with more identity work (McLean et al 2017). Specifically, it was found that those who develop alternative narratives made a greater number of explicit connections between life events and their selves and displayed higher levels of identity exploration.…”
Section: Introductionmentioning
confidence: 99%